A new history of early Christianity - Freeman, Charles (Yale Univ. Press, 2009)
Introduction -- Part one: Beginnings -- A trial -- The seedbed : Judaism in the first century AD -- Jesus before the Gospels -- Breaking away : the first Christianities -- From history to myth, from Jesus to Christ : what did Paul achieve? -- The letter to the Hebrews -- Fifty years on the Jesus of the Gospels -- John and the Jerusalem Christians -- Creating a New Testament -- No second coming : the search for stability -- Part two: Becoming Christian -- Toeholds in a wider empire : infiltrating Greek culture -- Open borders : the overlapping worlds of Christians and Jews -- Was there a gnostic challenge? -- The idea of a church -- To compromise or reject -- Celsus confronts the Christians -- The challenge of Greek philosophy -- Origen and early Christian scholarship -- New beginnings : the emergence of a Latin Christianity -- Victims or volunteers : the problem of Christian martyrdom -- The spread of Christian communities -- Part three: The imperial church -- The motives of Constantine -- Debating the nature of God -- Theodosius and the stifling of Christian diversity -- The assault on paganism -- 'No one is honoured before him' : the rise of the bishop -- An obsession with desire : Jerome and the temptations of the flesh -- The end of optimism : Augustine and the consequences of sin -- Divine but human -- The closing of the schools, Justinian and the silencing of debate -- A fragile church : Christianity and the collapse of the western empire -- Faith, certainty, and the unknown God